Fluorine-Lean Phosphonated Polymers of Intrinsic Microporosity with High Oxygen Permeability as a PEMFC Catalyst Layer Ionomer - Stigler, Theresa; Nemeth, Tamas; Fortin, Patrick; Thiele, Simon; Kerres, Jochen (ACS Applied Energy Materials, 2025)
An essential component of proton exchange membrane fuel cell (PEMFC) technology is the catalyst layer ionomer, serving as the binder and transport matrix responsible for the macroporous electrode structure and the regulation of proton and reactant gas supply to the catalyst interface. To improve the mass transport properties of the catalyst layer, we developed a fluorine-lean phosphonated polymer of intrinsic microporosity (pPIM). The highly kinked structure of the pPIM results in an ionomeric network with increased porosity to promote enhanced gas diffusion through the ionomer layer, while the incorporation of phosphonic acid head groups provides efficient proton conduction. Increased gas permeability of the ionomer is an important factor for effectively mitigating local transport losses that typically occur at high current densities. In situ PEMFC tests were carried out where the pPIM was utilized as the ionomer in the catalyst layer on both the anode and the cathode side. The ionomer-to-carbon (I/C) ratio was varied to evaluate its impact on the oxygen diffusion coefficient and overall fuel cell performance. A higher oxygen diffusion coefficient was achieved with the pPIM using an I/C ratio of 0.2, compared to the Nafion-based catalyst layer.
CRIS-Team Scopus Importer:2025-04-11
Keywords: catalyst layer; fluorine-lean; ionomer; oxygen diffusion coefficient; PEMFC; polymer of intrinsic microporosity